Quality of Life of Patients with Liver Cirrhosis - María Belén Alvarado Villavicencio; Evelyn Carolina Betancourt Rubio; Luis Roberto Villamarín Ponce (Revista Finlay)
Foundation: liver cirrhosis is a chronic liver disease characterized by the formation of scar tissue and a decrease in normal liver function. The quality of life of patients with liver cirrhosis may be affected due to the chronic nature of the disease and the possible associated complications. Objective: to analyze the quality of life perceived by patients with cirrhosis, as well as to examine the factors that generally influence their quality of life. Method: a descriptive, analytical and correlational, cross-sectional study was carried out with a sample consisting of 40 patients with liver cirrhosis. The main tool for data collection was the survey. Comparative analyzes were performed to evaluate perceptions of quality of life, health, and other vital domains based on demographic variables. Statistical tests such as Spearman correlation, Mann-Whitney U test and Kruskal-Wallis test were used, as appropriate for each variable. The results were shown in graphs and tables expressed in values and percentages. Results: in the study carried out, statistical significance was found between the level of education and the physical, psychological and environmental domains, likewise, statistical significance was observed between the sex of the subjects and the psychological and social domains, in addition, it was found statistical significance between comorbidities and the psychological, social and environmental domain. Conclusions: patients differed in the evaluative criteria of their quality of life. Factors such as: sex, education and coexisting diseases showed influence on the quality of life of patients with cirrhosis.